Epidermal nevus of the vulva/Genital warts. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Warts can affect the vulvar region, are often early, even in the first months of life, and persist for a long time, sometimes requiring differential diagnosis from epidermal nevus.